METHODICAL APPROACHES TO EVALUATION OF FINANCIAL EFFICIENCY OF PUBLIC-PRIVATE PARTNERSHIP - Григорська, Олена (Socio-economic relations in the digital society, 2019)
It is proved that the fi nancial interest of the state as one of the parties to the PPP is to maximize the PPP efficiency indicators due to the receipt of payments to the budget, and the importance of PPP eff ectiveness indicators for private partners is inversely related to the amount of payments they pay to the budget. It is proposed to achieve a balance of fi nancial interests of PPP participants by regulating the amount of concession payments to the budget by establishing a «financial equilibrium point». Th e latter is the amount of concession payments in which the net present value of the PPP project calculated for the concedent is equal to the net present value of the PPP project, calculated for the concessionaire. In the article, the eff ectiveness of PPP implementation is assessed through the financial feasibility of achieving the goal of PPP from the point of view of each of the interested parties with the help of indicators such as the profi tability index; net present value; internal rate of return; discounted payback period. In addition, it is proposed to calculate the index of the balance of fi nancial interests of PPP participants on the basis of calculating the similarity coefficient of financial efficiency vectors for the state and private partner.